Music for the Pria Dewasa: Changes and Continuities in Class and Pop Music Genres - Emma Baulch (Journal of Indonesian Social Sciences and Humanities, 2010)
This paper presents Rolling Stone Indonesia1 (RSI) and places it in an historical context to tease out some changes and continuities in Indonesian middle-class politics since the beginning of the New Order. Some political scientists have claimed that class interests were at the core of the transition from Guided Democracy to the New Order, and popular music scholars generally assert that class underlies pop genre distinctions. But few have paid attention to how class and genre were written into Indonesian pop in the New Order period; Indonesian pop has a fascinating political history that has so far been overlooked. Placing RSI in historical perspective can reveal much about the print medias classing of pop under New Order era political constraints, and about the ways these modes of classing may or may not have endured in the post-authoritarian, globalised and liberalised media environment